A Practical HPLC Method to Measure Reduced (GSH) and Oxidized (GSSG) Glutathione Concentrations in Animal Tissues - Yilmaz, Okkes; Keser, Serhat; Tutzcu, Mehmet; Guvenc, Mehmet; Cetintas, Buket; Irtegun, Sevgi; Şahin, Kazım (Medwell Online, 2009)
Glutathione is a tripeptide ubiquitously distributed in living cells, which play an important role in the intracellular protective mechanism against oxidative stress. There are many methods for glutathione analysis including spectrophotometric, fluorometric and bioluminometric assays, often applied to HPLC. In this study, an improved and modified method to measure reduced and oxidized glutathione (GSH and GSSG, respectively) concentrations in animal tissues has been developed. In the study, quail and rat tissue samples were homogenized with the mixture of 10 mM ETDA and 50 mM NaClO(4)0.1% H,PO, buffer. Proteins were precipitated by the addition 5% metaphosphoric acid. 50 mM NaClO(4)0.1% H3PO4 was used as mobile phase and Discovery RP-Amide C 16 was used as HPLC column. Glutathione molecules were separated at 215 nm by the UV detector. GSH molecule was eluded between 2.3 and 3 min and GSSG molecule was eluted between 3.5 and 4.5 min from the column. It was observed that in low level of glutathione molecules was detected by this process. Recovery rates of GSH and GSSG were 99.32 and 90.29%, respectively. In conclusion, this method is speed, sensitive and achieved since, it doesn't need forward derivatization process in contrast to many HPLC methods used for glutathione analysis.
Keywords: GSH; GSSG; HPLC method; liver; wistar rat